Role of caspases and CD95/Fas in the apoptotic effects of a nucleotide analog PMEG in CCRF-CEM cells - Mertlíková-Kaiserová, Helena; Votruba, Ivan; Matousová, Marika; Holy, Antonín; Hájek, Miroslav (Anticancer research, 2010)
BACKGROUND/AIM: 9-[2-(phosphonomethoxy)ethyl] guanine (PMEG) is a guanine acyclic nucleotide analog whose targeted prodrugs are being investigated for chemotherapy of lymphomas. Its antiproliferative effects have been attributed to cell cycle arrest and induction of apoptosis, however, the underlying mechanisms remain poorly understood. The objective of this study was to determine the requirements for caspase and CD95/Fas activation in PMEG-induced apoptosis. Additionally, the influence of PMEG on cell cycle regulatory proteins was explored. MATERIALS AND METHODS: CCRF-CEM cells were exposed to PMEG with/without caspase inhibitor or anti-Fas blocking antibody and assayed for phosphatidyl serine externalization, mitochondrial depolarization and the cleavage of procaspase 3 and the nuclear protein poly (ADP-ribose) polymerase (PARP). RESULTS: Despite an observed increase of caspase 3, 8 and 9 proteolytic activity, neither pretreatment of the cells with cell-permeable caspase inhibitors nor blocking the death receptor with anti-Fas antibody did prevent apoptosis induced by PMEG. CONCLUSION: PMEG-induced apoptosis is caspase- and CD95/Fas-independent.
Keywords: onkogenní proteiny; T-Lymphocytes; membránový potenciál mitochondrií; antigeny CD95; S Phase; inhibiční proteiny cyklin-dependentních kinas; aktivace enzymů; Enzyme Activation; Dose-Response Relationship, Drug; Guanine; cyklin-dependentní kinasy; vztah mezi dávkou a účinkem léčiva; Humans; Organophosphorus Compounds; mitochondrie; Cyclin E; kaspasy; Mitochondria; buněčný cyklus; cyklin E; Oncogene Proteins; Cell Cycle; Cyclin-Dependent Kinase Inhibitor Proteins; organofosforové sloučeniny; Cell Line, Tumor; S fáze; nádorové buněčné linie; apoptóza; Caspases; fas Receptor; lidé; Membrane Potential, Mitochondrial; T-lymfocyty; Signal Transduction; Cyclin-Dependent Kinases; Apoptosis; guanin; signální transdukce